Penerapan budaya 5S (senyum, salam, sapa, sopan, santun) di Madrasah Aliyah Negeri 3 Kediri - Al Fikri, Moch Hafidz (Maliki Interdisciplinary Journal, 2024)
To create a learning environment that is conducive and also to create positive relationships between individuals in the madrasah environment, there needs to be an organizational culture. 5S culture (smile, greeting, politeness and manners) plays an important role in the educational environment. In its application, 5S culture requires interactions between individuals that are friendly, polite and also mutually respectful between individuals. The aim of this research is to explore the application of 5S culture in the educational environment, in this case MAN 3 Kediri. The results of research and observations show that MAN 3 Kediri is able to apply 5S culture in the madrasa environment, both among students, teachers and school staff respect each other. Furthermore, this 5s culture can be applied to the general public, and students not only apply it in the school and home environment, but in their lives and also when they interact on a daily basis widely to other educational institutions, so that it is hoped that they can build a quality organizational culture.